Examination of evaluation index of tennis racket selection with stroke motion analysis - Sekine, N.; Takehara, S.; Suzuki, K. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this paper is to build a selection index for tennis rackets. Tennis rackets were evaluated using motion indices derived by investigating the effects of rackets on stroke movement. The subjects of this study were three male senior tennis players and two male beginner players. Stroke motion and the three-dimensional information of each part of the human body was measured with 12 motion capture cameras and 6 rackets with different characteristics. By using three-dimensional information, characteristic markers of the tennis strokes were derived. The vertical position of the marker was analyzed, and the change in the stroke motion of each racket was examined. The analysis was performed by comparing the sum of standard deviation and swing speed. As a result, the relationship between the sum of the standard deviation and the swing speed for the stroke motion was shown. It was suggested that a racket suitable for beginners may be presented by presenting the sum of the standard deviation of the z-axis position of the right wrist marker, which has a high correlation with the swing speed, as a racket index.